The Use of Vitamin D in Heart Failure Management: A Literature Review - Ratu Bertha Sofiani; Novita Carolia; Wiwi Febriani; Juspeni Kartika (Lembaga Pengembangan Kinerja Dosen, 2025)
Heart failure is a clinical syndrome characterized by structural or functional cardiac dysfunction that leads to hemodynamic disturbances and increased morbidity and mortality. Vitamin D, a prohormone with a vital role in metabolism, is known to exert cardioprotective effects through anti-inflammatory and anti-fibrotic mechanisms, modulation of calcium homeostasis, and inhibition of the renin–angiotensin–aldosterone system. Vitamin D deficiency has been shown to be highly prevalent among patients with heart failure and is correlated with poorer clinical outcomes. Numerous preclinical studies support the protective role of vitamin D against ventricular remodeling and myocardial hypertrophy; however, clinical trials in humans have yielded inconsistent and often contradictory findings regarding its effects on systolic function, surrogate parameters, and primary outcomes such as mortality and hospitalization. Consequently, vitamin D supplementation cannot yet be recommended as a standard therapy for heart failure, except in patients with confirmed deficiency. Further research with robust methodologies and stratified populations remains essential to elucidate its potential clinical benefits.